Technology Innovations in Right Upper Limb Rehabilitation: A Look at Physiotherapy and Occupational Therapy Tools - Madani, Sultan Fahad; Bedaiwi, Mazen Abdulaziz; Alghamdi, Raeed Abdullah; Shabaan, Abdulrahman ahmed; Almalki, Abdulaziz Mohammed; Albalawi, Riyadh Ibrahem (Journal of Ecohumanism, 2024)
This essay explores the right upper limb rehabilitation with the use of innovative technologies. It focuses on the consideration of what technologies are currently available and highlights the physiotherapy and occupational therapy tools that can be integrated together. After the stroke, rehabilitation therapy is essential for the patient’s improvement. Therefore, it is important to have a tool that helps with the rehabilitation therapy of the right upper limb. As an appropriate tool, technology innovation is considered and researched. This essay discusses the thoughts, ideas, applications, and designs of technology innovations in the right upper limb rehabilitation. Physiotherapy and occupational therapy are two different rehabilitations focusing on the same problem, which means they can be integrated together. Having tools that integrate both physiotherapy and occupational therapy together will help with the patient’s recovery. Innovative technology trends that can be used in the rehabilitation of the right upper limb are researched and discussed in this essay. Only the upper limb rehabilitation is being considered, while the lower limb rehabilitation is neglected. In addition, it focuses mainly on stroke patients, and other diseases that affect the upper limb are neglected. Tools that are designed to help with the right upper limb rehabilitation are discussed. For the tools, there must be a consideration of whether the tool is for rehabilitating the right upper limb or whether the technology is integrated together for rehabilitating the right upper limb. In addition, whether the tool is designed or something that already exists is also considered. Most tools are designed and newly developed technologies. Some tools are already in use and are being improved by the new technology approach. Another consideration is whether the technology is focusing on the end-user, which is essential for the technology innovation on the rehabilitation tools being explored (Batista e Siqueira et al., 2024). The focus of the technology tools is to provide rehabilitation to the end-user, who is the patient. It is important that tools used in rehabilitation are adaptive and easy to use to help the rehabilitation process.